Comparison of stingless bee honey and silver sulfadiazine on diabetic wound healing in rat models - Fajari, Nanang Miftah; Pranoto, Agung; Perdanakusuma, David Sontani; Prenggono, Muhammad Darwin; Rudiansyah, Mohammad; Nur'amin, Hendra Wana; Syarifa, Yulia; Hasrianti, Nuvita; Saputri, Imelda Nita; Afrianto, Muhammad Irawan; Husna, Annisa Halida (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Diabetic foot ulcers (DFUs) are a major health concern in Indonesia. Adjuvant therapies may improve healing by avoiding secondary infections, promoting angiogenesis, and supporting oxygen circulation. This aimed to evaluate the effect of stingless bee honey (SBH) from Heterotrigona itama on diabetic wound size in rats (Rattus norvegicus), compared to silver sulfadiazine (SSD). METHODS An experimental study was conducted on 13 diabetic wounds in streptozotocin-induced diabetic rats treated with three types of therapies: SSD (n = 5), pure SBH (n = 5), and SBH with 20% water content (n = 3). The study initially involved 21 rats, but eight died during the diabetes modeling and wound observation phases, presumably due to hyperglycemia. Baseline characteristics did not differ significantly across the groups. RESULTS SBH with 20% water content and pure SBH reduced wound size by 95.1% and 92.1%, outperforming SSD (77.4%), with all therapies showing statistically significant improvement (p<0.05). However, the differences between groups were not statistically significant (p = 0.162). CONCLUSIONS Topically applied SBH is a potential natural therapeutic agent for diabetic wounds, in addition to standard treatment such as SSD.